Småskalig livsmedelsförsörjning av mjölk - Pallars, Olle (2005)
During the last year's Swedish agriculture have had difficult times, with decreasing prices and at the same time increasing production costs, which has led to bad profitability and faith in the future. The dairies in Sweden have also had a rough time and there have been large rationalizations during the years. In the beginning of the 20th century there were almost 1700 diaries in the Swedish countryside. There has been a large technical development during the 20th century resulting in a decrease in diaries to only 46 in the whole country today. They are owned by 15 diary companies, of which 7 large and dominate on the market and the rest are small-scale companies. With this development the confidence and feeling for the diary companies also has decreased. Today it doesn't matter for the customer from who they buy their milk products from because it has become a bulk commodity. This has created an opportunity for the farms that want to process their own products. When the customer buys these products he/she knows were the raw material comes from and who has processed it. This gives the product a higher value for the customers, which in the end gives a better income to the producer. The research I have done shows that the interest for locally produced, small-scale products has increased in Sweden during the last years. During the last four years the number of small-scale diaries has increased to the double and today there are 80 spread over almost the whole county. There are two exception, Jämtlands- and Västra Götalands County where 30 of the 80 diaries are located. These 80 diaries are the ones that have permission to sell their products to retailers. Besides these companies there are many small diaries that just have permission to sell their products on the own farm or on markets. The demand for these products seems to increase for each year. To get permission to process a product, you need to have a premises that are approved by the local environmental office. These premises shall follow the regulation that the National Food Administration have set up to guarantee a safe product to the consumers. For the products that are sold directly to the consumer, the producer can get the premises approved according to the regulations in SLVFS 1996:6 plus 4, 13, 18, 24, 27 § in SLVFS 1994:13, reprinted 1998:41. If the selling should go through a retailer you should instead use the regulation SLVFS 1994:13, reprinted 1998:41, and you also have to apply for a control number. These regulations will only be valid until the 1st of January in 2006 when there will be new regulations from the EG. There will probably not be any significant change in the rules except that the concept "from soil to table" will be more important. Because there should not be any misunderstandings in the planning of the premises, the local environmental inspectors and counsellors should be contacted as early in the process as possible. At The National Food Administration and LRFs websites you can find lots of information on food processing.